2021
DOI: 10.1177/13524585211031791
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of comorbidities at diagnosis in immigrants with multiple sclerosis

Abstract: Background: Multiple sclerosis (MS) has been associated with certain comorbidities in general population studies, but it is unknown how comorbidity may affect immigrants with MS. Objective: To compare prevalence of comorbidities in immigrants and long-term residents at MS diagnosis, and in matched control populations without MS. Methods: We identified incident MS cases using a validated definition applied to health administrative data in Ontario, Canada, from 1994 to 2017, and categorized them as immigrants or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Other special populations with MS, including underrepresented ethnic and immigrant populations, also seem disproportionately affected by comorbidity. Although immigrants often have fewer medical conditions than the general population (‘the healthy immigrant effect’), immigrants with MS in Ontario, Canada had a higher prevalence of mood and anxiety disorders, migraines, diabetes, IHD, and chronic obstructive pulmonary disease compared to controls ( 21 ). In studies from the United States, depression and anxiety were more frequent in Black and Hispanic/Latinx individuals with MS ( 22 , 23 ).…”
Section: Prevalence Incidence and Comparisons With Other Populationsmentioning
confidence: 99%
“…Other special populations with MS, including underrepresented ethnic and immigrant populations, also seem disproportionately affected by comorbidity. Although immigrants often have fewer medical conditions than the general population (‘the healthy immigrant effect’), immigrants with MS in Ontario, Canada had a higher prevalence of mood and anxiety disorders, migraines, diabetes, IHD, and chronic obstructive pulmonary disease compared to controls ( 21 ). In studies from the United States, depression and anxiety were more frequent in Black and Hispanic/Latinx individuals with MS ( 22 , 23 ).…”
Section: Prevalence Incidence and Comparisons With Other Populationsmentioning
confidence: 99%
“…Immigrants and descendants may have different characteristics such as socioeconomic factors like educational level, income, and family structure influencing the risk of comorbidities, but also a different susceptibility for MS and comorbidities in general ( 51 ). A study investigating comorbidities found a higher prevalence among immigrants compared to long-term residents underlining the importance of taking ethnicity into account when investigating the consequences of MS ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…8,16 As compared to long-term residents, immigrants to Ontario, Canada have an increased prevalence of comorbidity at the time MS is diagnosed, including mood/anxiety disorders, schizophrenia, diabetes, hypertension, ischemic heart disease, chronic lung disease, migraine, epilepsy, inflammatory bowel disease, and rheumatoid arthritis. 20 Lower socioeconomic status is associated with an increased incidence and prevalence of psychiatric comorbidities including depression, anxiety, bipolar disorder, and schizophrenia. 21 It is also associated with an increased incidence and prevalence of physical comorbidities.…”
Section: Which Comorbidities Affect People With Ms and How Often Do T...mentioning
confidence: 99%
“…As compared to long-term residents, immigrants to Ontario, Canada have an increased prevalence of comorbidity at the time MS is diagnosed, including mood/anxiety disorders, schizophrenia, diabetes, hypertension, ischemic heart disease, chronic lung disease, migraine, epilepsy, inflammatory bowel disease, and rheumatoid arthritis. 20 …”
Section: Who Is At Risk?mentioning
confidence: 99%